Karakteristik Pendidikan Luqman Hakim dalam Al-Qur’an Surat Luqman Ayat 13-17 - Ahmad Fauzi (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2019)
The main reference in the concept of Islamic education is the Qur'an in surah Luqman, which is a letter that is referred to the name of a man who activity and wise in educating his son. He has a concept of education that can build spiritual intelligence in the child, so that Allaah perpetuates some words that contain wisdom from them in the Qur'an, so that they can be learned from the lessons and benefits. Using the Library study method, the study found that the education characteristic of Luqman Hakim as contained in the letter of Luqman verses 13-17, namely: (1) The education of Luqman Hakim about the Tauhid such as prohibition of shirk (purification of the soul of haughty and prideful nature); (2) Individualized morality such as gratitude, patience, safeguarding, doing good to parents and establishing prayers. (3) Social morality that is implemented with the practice of Amar Ma'ruf nahi Munkar.